Harper's Round Table, January 24, 1882 - Various (Salt Lake City, UT : Project Gutenberg, 2016)
"Harper's Round Table, January 24, 1882" by Various is a periodical publication likely compiled during the late 19th century, specifically in the Victorian era. It is a collection of children's stories, poems, and articles that explore various themes of childhood adventures, nature, and moral lessons. The content provides insights into the lives and imaginations of children at that time. The book features a variety of narratives that engage young readers with compelling characters and lessons. One notable story, "A Country Boy in Winter," captures the joys of sledding and the carefree spirit of childhood during winter months. Another story, "Todd and Ketchum's 'Grate Show,'" depicts two boys who put together a circus, showcasing their creativity and humor in the face of chaos. Other contributions include educational pieces about nature and cautionary tales concerning smoking, reflecting the societal values and concerns of the era. Overall, this collection presents a delightful mix of entertainment and education aimed at young audiences, fostering imagination and moral development. (This is an automatically generated summary.)
Release date is 2016-08-07
Produced by Annie R. McGuire
Keywords: Children's periodicals